Modeling and optimization in tribological parameters of polyether ether ketone matrix composites using D-optimal design. (February 2016) - Rajmohan, T; Palanikumar, K; Davim, JP; Premnath, A Arun
Fiber-reinforced polymer composites are nowadays used in numerous applications due to their good tribological, mechanical, and thermal properties. In the present investigation, the tribological behavior of polyether ether ketone (PEEK) and PEEK reinforced with glass fiber (GF) has been investigated using the pin-on-disk wear tester under dry sliding condition at different applied loads, speeds, and sliding distance. Modeling and optimization of tribological parameters is carried out using response surface methodology (RSM)-based D-optimal design. Tribological parameters such as load, sliding speed, and sliding distance are chosen as numerical factor, and the weight percentage of GF content is considered as the categorical factor. An experimental plan of four-factor (three numerical + one categorical) D-optimal design based on the RSM is employed to carry out the experimental study. The wear performances of PEEK matrix composites are evaluated using the performance indicators such as specific wear rate and coefficient of friction. The morphologies of the worn surfaces are observed using scanning electron microscopy and atomic force microscopy.